Effects of punishment, social norms, and peer pressure on delinquency: Spare the rod and spoil the child?. (September 2019) - Chadee, Derek; Ali, Stacia; Burke, Ariel
Parental behavior regulation and delinquency is well established in the literature. While the precise direction of the relationship seems elusive, delinquency remains a recurring behavioral outcome of punitive forms of discipline. Opponents of punishment propose that it leads to a greater likelihood of conduct issues in adolescence and adulthood. The present study assessed the influence of punishment, social norms, and age on delinquency while examining peer pressure as a mediator. Further, gender and ethnicity were controlled. A random sample of 2011 participants from a southern Caribbean island responded to a questionnaire administered by field interviewers. Data were analyzed using path analysis, multiple group analysis, and one-way analysis of variance. Results showed that all independent variables were significant in predicting delinquency while peer pressure mediated these relationships. Further, gender and ethnic differences were observed with males and African-Trinidadians rating highest on delinquency. Findings are discussed within the theoretical frameworks of social bond theory, PARTheory, and in relation to previous research. Limitations and future research are also highlighted.